FIRST RESULTS OF THE SEISMIC TOMOGRAPHIC GEOTRAVERSE "VINNYTSIA – TAGANROG" RESEARCH - Pigulevskiy, P.; Shumlianska, L.; Dubovenko, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Methodological aspects and results of studying of the stratigraphic section of the upper mantle along the seismic tomographic geotraverse "Vinnytsia – Taganrog" are considered in the article. To localize mantle anomalies associated with changes in the composition, density of the substrate, temperature, etc., an analysis of the curves of the first and second velocity gradients was used to search for the inflection points of the vp curve. A velocity curve was obtained by constructing a seismotomographic model using the Taylor approximation method. Before the curvature analysis, a smoothing procedure was carried out in accordance with the wavelength. This procedure is important for screening false anomalies, the size of which is responsible for Fresnel zones, since the resolution of the seismic wave has the dimension of the Fresnel zones. According to this technique, the curves of the first and second velocity gradients vp were calculated for the upper mantle under the main tectonic structures of the Ukrainian Shield along the "Vinnytsia – Taganrog" geotraverse. The profile crosses the Podol, Bug megablocks, Golovanev suture zone, Ingul megablock, Kryvyi-Rih-Kremenchug suture zone, Middle-Dnipro megablock, Orekhovo-Pavlograd suture zone and Azov megablock. According to the results, the most significant features of the mantle structure were identified in the depth interval of 50–750 km. A transregional tectonic zone was distinguished (between points 30.0E, 49N and 32.0E, 48.25N), over which the Golovan suture zone (GSZ) and the eastern part of the Bug-Ros megablock and the western part of Ingul, where significant violations of the common mantle border of 660 km are observed – a border between the upper and middle mantle. Under the Podol megablock, this border is located at a depth of 550–560 km. Under GSZ it rises to 450–460 km, and to the east of the suture zone it drops sharply to 660-670 km, where it takes a subhorizontal position. A sharp jump to marks of 450–460 km shows the global breakdown zone and the nature of the contact between different geodynamic mantle regions under the modern platform.
Keywords: gradient analysis; mantle boundaries; geodynamics